The Protective Effects of Vitamin E on Ischemic Neuronal Damage in Rats - Tilokskulchai, Kanokwan; Shuprisha, Jantana; Limviwatkul, Rachawan; Nualplub, Suparp; Ninturk, Ratana (Journal of Basic and Applied Pharmacology, 2015)
Antioxidant vitamins (i.e. vitamin E and vitamin C) in large dosages are increasingly common self-prescribed drugs. This increase in vitamin use has, perhaps, been promoted by the claim that vitamin may provide protection from ischemic brain damage or prevent age-associated diseases induced by free radicals and lipid peroxidation. Apart from such legitimate uses of mega-dosages of vitamins, at present there is no conclusive evidence to support the recommendation of such use. Therefore, the purpose of the present study is to investigate the efficacy of short-term and long-term vitamin E supplements in protecting brain damage from transient global cerebral ischemia in Spraque Dawley rats. The present study was designed to examine vitamin E's effect on histological outcome 7 days after transient global cerebral ischemia in the treated and untreated animals. Global cerebral ischemia was induced by 30 minutes bilateral occlusion of common carotid arteries with lowering mean arterial blood pressure to 60-80 mmHg before occlusion. For the short-term study, animals were divided into two groups. Group 1 was subjected to cerebral ischemia with no medication and group 2 was fed daily with vitamin E (30 mg/kg) from 2 weeks before to one week after ischemic insult. For the long-term study, global cerebral ischemia was induced in group I at the age of 15-19 months with no medication. Group 2 was fed daily with vitamin E (30 mg/kg) for 12-15 months before ischemic insult beginning from the age of 3 months. The result demonstrated that the mean percentage of cell death in the 2 weeks supplement group (17.8±0.8) was significantly less than that of the untreated group (28.0±0.8)(P<0.05). However, the cell death in the long-term (12-15 months) vitamin E supplement group was not significantly different from the untreated group. The present study, therefore, revealed that short-term vitamin E supplement provided partial protective effect from acute ischemic brain damage. In contrast, our results also showed that long-term vitamin E supplement could not influence the outcome damage induced by transient ischemic attack. Therefore, vitamin E supplement should not be recommended in healthy elderly population. It should be reserved for individuals with documented deficiency or who are at risk only.